The development of a scale to measure orthorexia nervosa - Kramer, Melanie E., author; Rickard, Kathryn, advisor; Conner, Bradley T., committee member; Wdowik, Melissa, committee member (Colorado State University. Libraries, 2016)
Due in part to the obesity epidemic occurring today in the United States, the public discussion of healthy eating has become an emerging social trend (Chaki et al., 2013). Evidence suggests that since the importance of healthy eating has been increasingly emphasized, individuals have become more aware of how their diet impacts their overall health, and many have attempted to adjust their food choices (Bagci Bosi et al., 2007; Nicolosi, 2006). It has been suggested that, for some, healthy eating has been taken to the extreme, resulting in social, physical, and psychological consequences (Chaki et al., 2013). The term Orthorexia Nervosa (ON) was originally developed by Steven Bratman; he conceptualized ON as a way to describe an obsession about proper nutrition and a "fixation" on healthy eating (Bratman & Knight, 2000). Currently, very little is known about ON as a construct, and neither a formal operational definition nor standard diagnostic criteria of ON exist. Although, there are two scales that measure ON (Donini, 2007; Gleaves et al., 2013), neither scale seems to fully capture this phenomenon. This study will attempt to develop a valid and reliable scale, the Orthorexia Nervosa Scale (ONS), to more accurately and fully capture the construct of ON. The first step was the development of the ONS items, which included a thorough review of the literature and consultation with experts in the field. 103 items were retained to form the initial version of the ONS. Using a development sample (n = 712), I conducted a parallel analysis on the items. An exploratory factor analysis (EFA) was also conducted and items were selected according to their psychometric quality. The EFA revealed a 10-factor structure with 47 items. The second step was conducting a confirmatory factor analysis on the data from a second development sample (n = 397). Analyses indicated a good model fit of the 47-item, 10-factor scale after making model modifications. This measure will be a useful tool in future research and clinical work related to ON. A new, more comprehensive, measure of ON which captures all of its components could lead eventually to improved treatment for these individuals.